Pelancongan Marin: Impak Aktiviti Selam Skuba dan Snorkeling Terhadap Aktiviti Keusahawanan, Sosioekonomi dan Alam Sekitar (Sains Humanika, 2012)
Marine tourism is one of the main factors contributing to the growth of the tourism sector in Malaysia. This is because Malaysia is among countries which has most beautiful islands in the world, with a diversify of marine life. It attracts visitors to explore and enjoy the beautiful views of the sea through scuba diving and snorkeling. These vibrant activities open business opportunities for local residents, but is also said to have negative impacts on environmental sustainability, particularly to the coral reefs and undersea life. Thus, a preliminary study was conducted in Pulau Pangkor, Perak to explore local perceptions about the impact of marine tourism activities such as diving and snorkeling on entrepreneurship, socio-economic wellbeing and also to environmental sustainability. This study involved 40 local people who live and work on Pangkor Island. This is an exploratory study, using questionnaire as the instrument. Findings showed that locals perceived marine tourism such as scuba diving and snorkeling activities have high impact on entreprenuerial activities and socio-economic wellbeing of Pangkor Island residents and moderate impact to environmental sustainability.
Keywords: Scuba diving; snorkeling; marine tourism; environmental sustainability; entrepreneurship